LEARNING MODEL APPLICATION SQ3R (SURVEY, QUESTION, READ, RECITE, REVIEW) TO IMPROVE STUDENT LEARNING OUTCOMES IN THE SUBJECT MATTER OF PRODUCTIVE MAINTENANCE OF BATTERY FOR CLASS X TSM SEMESTER II SMK KARSA MULYA PALANGKARAYA 2015/2016 ACADEMIC YEAR (Jurusan Pendidikan Teknologi Dan Kejuruan, 2017)
The cooperative model with SQ3R learning model is a learning design which is able to develop and shape the positive character of students. The purpose of this research is to find: (1) Teacher’s role to student in unterstanding the learning after using cooperative learning by applying the SQ3R learning model, (2). The completeness of student’s learning outcome, and (3) Student’s response in understanding the battery maintenance subject after applying SQ3R Model. This research adopted the descriptive research type in which the sample was using whole students of class x at second semester in SMK Karsa Mulya Palangka Raya at academic year 2015/2016. The sample was selected from population by using class sample (class X) at about 34 students involving the instruments such as observation of teacher’s role to students, cognitive learning outcomes test, and the questionnaire of student’s response. The data analyis result indicated that the ability in understanding the application of SQ3R learning model is by an average percentage of first meering at about 91.66 % categorized as excellent, second meeting at around 62.72 % categorized as good, third meeting at about 93.75 % categorized as excellent, and fourth meeting at about 92.70 % categorized as excellent. The individually cooperative learning model obtained by 28 studnets as passing grade status and 4 students experiencing the failed result. Classically, the learning stated is complete with percentage at about 87.50 % successful students. The passing grade of TPK gotten by 19 TPK or at 68.75 % as complete result from 35 TPK. The student’s response to the battery maintenance by applying SQ3R model was expressing the interest to learning model conveyed with percentage at 90.60 %.